Social Measure Influencing Familial Securities of HIV Patients in Nongbualamphu in 2008 - ศุภรัตนกุล สังคม; อายุวัฒน์ ดุษฎี (Disease Control Journal, 2009)
The main objective of this study was aimed for developing model of the familial security of HIV infectious. Type of study were mixed-methods with cross sectional study. Data was collected during 1 May - 30 June 2008 by questionnaire. The sample size were 370 sample.The resulted of study showed that the familial security of HIV infected were three levels. First, the high level, consisted of health insurance 68.6%, healthy right 70.8% and good association in families 55.1%. Second, themoderate level consisted of the emotionally support 57.0%, the appraisal support 48.9%, the information support 41.9%, the reinforcing support 41.9% and human right 51.1%, educatory right 54.1%, social welfare of government 36.2%, social welfare in local government 42.7, marriage norm 39.7, having failed marriage 57.8 and economic self reliance 63.2%. Third, the low level consisted of the freedom from fear 51.9%, freedom from need 54.9% and Non-government organization’s social welfare 65.9%. Moreover, the securities were influenced by human security ( =.14), social supporting ( =.-0.03), social right ( =.47), and social welfare ( =-0.02) of which the power of prediction was 78% (R2.78) The recommendation for the policy maker in society for development and human security was that the reconstruction model from this study should be developed for strategic planning and put on operation for road map for the families security of HIV infected peoples. The integration of organizing network of GO NGOs and Local government for re-engineering responsibility role should be developed followed by rebuilding social order for the families security of HIV infected peoples in human right. Finally, rebuilding province special unit for response welfare for the families security of HIV infected peoples should be establshed.